2008
DOI: 10.4085/1062-6050-43.6.565
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Resting Scapular Posture in Healthy Overhead Athletes

Abstract: Context: Observation of the scapular posture is one of the most important components of the physical examination in overhead athletes. Postural asymmetry is typically considered to be associated with injuries. However, asymmetry in the overhead athlete's scapula may be normal due to the dominant use of the limb.Objective: To quantify the differences in resting scapular posture between the dominant and nondominant sides in 3 groups of healthy overhead athletes (baseball pitchers, volleyball players, and tennis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
121
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 24 publications
6
121
4
1
Order By: Relevance
“…We used a clinical method of visual observation to evaluate uninjured professional baseball players for the presence of scapular dyskinesis using a scapular classification system recommended in the literature [6][7][8]19]. The presence of subtle scapular dyskinesis identified in laboratory studies [13,15] in overhead athletes coupled with the reported consequences of scapular dyskinesis on high-level overhead upper extremity function [6,7,9] highlight the importance of early identification and recognition of scapular pathology in overhead athletes to both prevent injury and optimize performance. The overall purpose of this study was to use a clinical method of visual observation to evaluate the scapula of uninjured professional baseball players to determine the interrater reliability of visual observation and the Kibler et al [8] scapular classification system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used a clinical method of visual observation to evaluate uninjured professional baseball players for the presence of scapular dyskinesis using a scapular classification system recommended in the literature [6][7][8]19]. The presence of subtle scapular dyskinesis identified in laboratory studies [13,15] in overhead athletes coupled with the reported consequences of scapular dyskinesis on high-level overhead upper extremity function [6,7,9] highlight the importance of early identification and recognition of scapular pathology in overhead athletes to both prevent injury and optimize performance. The overall purpose of this study was to use a clinical method of visual observation to evaluate the scapula of uninjured professional baseball players to determine the interrater reliability of visual observation and the Kibler et al [8] scapular classification system.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified alterations in scapular movement in healthy uninjured overhead athletes [10,13,15]. Myers et al [13] measured increased scapular upward rotation, internal rotation, and retraction in throwing athletes on their dominant throwing extremity as compared with a control group of nonthrowers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessment of scapular positioning is a theme has been emphasized in scientific literature [1][2][3][4][5][6][7][8][9][10][11] . Positioning and orientation of the scapula on thorax are important to centralize the humeral head and base for normal function of shoulder joint complex during daily and sport activities [5][6][7]9 .…”
Section: Introductionmentioning
confidence: 99%